THE EFFECTIVENESS OF BLENDED LEARNING IN IMPROVING 21ST CENTURY SKILLS IN MIDDLE SCHOOL STUDENTS - Baso Intang Sappaile; Samantha Gonzales; Andres Villanueva (Yayasan Adra Karima Hubbi, 2026)
Blended learning is frequently promoted as an effective instructional model for fostering 21st-century skills; however, much of the existing discourse assumes its superiority without adequately examining the contextual and pedagogical conditions that shape its outcomes. This study addresses this gap by investigating whether blended learning meaningfully improves critical thinking, collaboration, creativity, and digital literacy among middle school students in a real classroom environment. The research aims to evaluate not only the magnitude of improvement but also whether the observed changes can be attributed to the blended instructional design rather than external factors such as teacher expertise or students’ prior technological exposure. A quasi-experimental method was employed involving two groups of eighth-grade students: an experimental group receiving blended instruction through a combination of face-to-face learning, digital modules, and interactive online tasks, and a control group receiving conventional instruction. Data were collected through performance-based assessments, observation checklists, and student self-evaluation surveys. The analysis utilized paired-sample and independent-sample t-tests to compare pre- and post-intervention differences. The findings indicate a statistically significant improvement in all four targeted skills among the experimental group, with the strongest gains observed in digital literacy and collaborative problem-solving. However, the results also suggest that the effectiveness of blended learning is highly dependent on instructional scaffolding, the quality of digital resources, and students’ initial readiness for technology-mediated tasks. The study concludes that blended learning can enhance 21st-century skills in middle school students when implemented through a structured, well-facilitated design. It cautions, however, against assuming universal effectiveness across diverse learning environments.